植物油料蛋白木材胶黏剂改性的研究进展Research progress on modification of plant protein-based wood adhesives from oilseeds - 刘欣锐，陈惠，高强，李建章 LIU Xinrui， CHEN Hui， GAO Qiang， LI Jianzhang (Zhongguo youzhi, 2023)
植物油料蛋白胶黏剂具有来源广泛、无毒、可再生及制备简单等优点，但胶接强度低、耐水性能差、易霉变等问题限制了其发展和应用。综述了近年来几种主要植物油料蛋白胶黏剂如大豆蛋白胶黏剂、花生蛋白胶黏剂、棉籽蛋白胶黏剂等在木材行业的研究和应用现状，重点阐述了提高植物油料蛋白胶黏剂耐水性能的改性方法，包括物理改性、变性剂改性、接枝改性、交联改性、仿生改性、酶改性、纳米材料改性、复合改性等，指出了植物油料蛋白胶黏剂存在的问题，并对未来发展方向和应用前景进行了展望。Plant protein-based adhesives from oilseeds have the advantages of extensive sources, non-toxic, renewable and simple preparation. However, the development and application of this kind of adhesives are limited by the problems of low bonding strength, poor water resistance and easy mildew. The research and application progresses of several plant protein-based adhesives from oilseeds in the wood industry in recent years were reviewed, such as soy protein adhesive, peanut protein adhesive and cottonseed protein adhesive. The modification methods to improve the water resistance of protein adhesive were summarized, including physical modification, denaturant modification, grafting modification, crosslinking modification, biomimetic modification, enzyme modification, nanomaterial modification, composite modification and so on, and the problems of plant protein-based adhesives were pointed out. The future development direction and application prospects were put forward.